Women and Family Members’ Views Regarding Early Decisions about Breast Cancer Treatment: A Qualitative Study - Wan Hasliza Wan Mamat; Nikki Jarrett; Nur Alia Hairulisa@Mohd Hairi; Norfadzilah Ahmad; Ashikin Atan; Susi Lund (Nurse Media Journal of Nursing, 2023)
Background: Conventional or hospital treatment such as surgery, chemotherapy, or radiotherapy is widely recommended by health care providers for treating breast cancer. Early decision in conventional treatment is a complex phenomenon that requires careful consideration of the medical condition, available information, potential risk, financial, job, and involvement of family members. However, there is an inadequate understanding of early decisions about conventional treatment in Malaysia. Purpose: This study aimed to explore the early decisions about breast cancer treatment among women and their family members.Methods: This study employed a qualitative, narrative approach. Purposive and snowball sampling were applied, and 28 participants were recruited for this study. The participants took part in in-depth, face-to-face, and audio-recorded one-time interviews. All interviews were subsequently transcribed verbatim and analysed using narrative analysis.Results: This study identified two themes regarding early decisions about breast cancer treatment: (1) women and family members who accepted immediate conventional treatment, and (2) women and family members who refused immediate conventional treatment. This study discovered that some women and family members agreed to undergo conventional treatment immediately due to following doctors’ advice, influence by other patients with breast cancer, personal attitude, and appropriate knowledge concerning breast cancer. Meanwhile, other women refused it due to fear, not ready to undergo treatment, influenced by other people and socio-culture template. The unique finding in this study is the presence of specific socio-cultural templates related to breast cancer.Conclusion: This study highlights that health care providers can assist women who decline breast cancer treatment by offering education about conventional treatment options. This can be achieved by providing accurate information about the treatment, addressing treatment-related fears, providing emotional support, and encouraging open communication regarding the reasons for refusing conventional treatment.